1992
DOI: 10.1523/jneurosci.12-07-02865.1992
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous locomotor hyperactivity in a mouse mutant with a deletion including the Snap gene on chromosome 2

Abstract: The gene encoding the synaptosomal-associated protein--25 kDa (SNAP-25) was mapped by analysis of somatic cell hybrids and an intersubspecies backcross to mouse Chromosome 2. To identify potential mutants for SNAP- 25, mice bearing mutations mapping to this region of Chromosome 2 were screened for Snap gene abnormalities. Mice heterozygous for the semidominant mutation coloboma (Cm/+) were identified that carried a deletion of Snap gene sequence. Analysis of genomic DNA revealed that the Snap gene dosage in Cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 23 publications
4
88
0
1
Order By: Relevance
“…These results are consistent with the significant increase in SNAP25 protein level previously reported in Brodmann's area 9 (dorsolateral prefrontal cortex) in patients with BD, 15 as cellular and animal studies showed that variations in mRNA levels of SNAP25 correspond to equivalent variation in protein levels. 32,33 The SNP4 is located between two AP-1 consensusbinding sequences in a region that contributes to the repression of the SNAP25 transcription by binding of POU4F2 (also called Brn-3b). 30,34 This protein is a member of the Pict-Oct-Unc (POU) transcription factor family that involved in the development of the mammalian nervous system and for which an overexpression results in a failure of SNAP25 activation and neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are consistent with the significant increase in SNAP25 protein level previously reported in Brodmann's area 9 (dorsolateral prefrontal cortex) in patients with BD, 15 as cellular and animal studies showed that variations in mRNA levels of SNAP25 correspond to equivalent variation in protein levels. 32,33 The SNP4 is located between two AP-1 consensusbinding sequences in a region that contributes to the repression of the SNAP25 transcription by binding of POU4F2 (also called Brn-3b). 30,34 This protein is a member of the Pict-Oct-Unc (POU) transcription factor family that involved in the development of the mammalian nervous system and for which an overexpression results in a failure of SNAP25 activation and neurite outgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, coloboma mice have a 2 cM deletion on chromosome 2, including the SNAP25 gene. 32 Raber et al 12 studied the release of several neurotransmitters in heterozygous mice (Cm/ Ăž ), expressing 50% of the SNAP25 protein level, and showed that depolarisation failed to induce dopamine release and induced significantly lower than normal amounts of serotonin from the dorsal striatum. These results were recently confirmed by Fortin et al, 43 who showed that SNAP25 was required for dopamine release from rat neurons in culture.…”
Section: Discussionmentioning
confidence: 99%
“…18 The synaptosomal-associated protein of molecular weight 25 kDa (SNAP-25) was implicated in ADHD by studies on the mouse mutant strain coloboma (Cm/Ăž ). This radiation-induced mutant strain displays spontaneous hyperactivity that is suppressed by dextroamphetamine 19 and has thus been proposed as an animal model for ADHD. 20 The coloboma strain is hemizygous for a 2-cM deletion encompassing multiple genes, including SNAP-25.…”
Section: Introductionmentioning
confidence: 99%
“…8 Other characteristics include head bobbing, prominent eye dysmorphology, and paroxysmal circling activity. 9 Expression of a transgene encoding SNAP-25 rescues the hyperactivity but not the head bobbing or ophthalmic deformation 10 suggesting that the SNAP-25 gene is responsible for the observed hyperactivity but that the other characteristics of coloboma are the result of other genes in this deleted region. The coloboma strain is also delayed in some developmental milestones-the righting reflex and bar holding, a task designed to measure motor coordination.…”
Section: Introductionmentioning
confidence: 99%